The Effects of Marriage and Divorce on Women's Nationality in the Iranian Law - Seyed Mohsen Hashemi Nasab Zavareh (UIN Sunan Gunung Djati, 2023)
As the first and foremost social institution, the family significantly impacts its immediate larger society. Also, the importance of family as a key figure in a healthy society and the necessity of strong relations between spouses make it imperative to devise the required legal devices. As women are prone to suffer and receive more damage in cases of family breakdown, the legislator should develop and establish more protective statutes concerning women's rights. This study uses legal research methods with a qualitative approach. To protect Iranian women's rights, the legislator distinguishes cases where an Iranian woman marries a foreign man and those where Iranian men marry foreign women. In the former case, the wife's change, or retention, of nationality is subject to the laws of the husband’s State. In contrast, in the latter case, the legislator enforces the unity of nationality principle. Marriage between Iranian women and foreign men causes women to experience many changes and limitations regarding their national and inheritance rights. Also, they may lose their Iranian nationality due to their marriage —in cases when the husband’s nationality, due to the law of the husband's State, is forced upon the wife. On the other hand, foreign women married to Iranian men, though forced to accept Iranian nationality, encounter fewer limitations resulting from marriage. Upon Divorce, they are neither forced to accept a nationality, unlike when marriage is celebrated, nor denied their Iranian nationality. They can choose whether to remain an Iranian national or recover their original nationality.